Applying the Fuzzy Analytic Hierarchy Process Method to Evaluate Key Indicators of Health Promotion Policies for the Elderly in Taiwan - Ling-Mei Hsu (Hindawi Limited, 2021)
Investigation of the key indicators of health promotion policies for an aging society can shed light on the priority of the government’s health promotion efforts. This study applied the fuzzy analytic hierarchy process (AHP) method in an empirical analysis of the key indicators of the health promotion policies for Taiwan’s aging society. Based on a review of the literature and expert interviews, this paper first conducted a preliminary study and evaluation of major factors affecting health promotion policies and found 4 major evaluation aspects and 16 evaluation indicators. After employing an AHP expert questionnaire in an empirical investigation, the following findings were made: (1) “healthy living” was the most important evaluation aspect for Taiwan’s health promotion policies for its aging society. (2) The six leading key indicators of health promotion policies were “promotion of personal health awareness and behavior,” “promotion of home medical services,” “guaranteeing the economic security of the elderly,” “planning a family caregiver support service system,” “well-planned health promotion plans for the elderly,” and “training long-term care service personnel and providing professional medical care.” Following discussion, recommendations concerning these six key indicators are made as a reference for future evaluation of health promotion policies for an aging society.